Process modelling and techno-economic analysis of natural gas combined cycle integrated with calcium looping - Erans Moreno, Maria; Hanak, Dawid P.; Jordi, Mir; Edward, Anthony; Manovic, Vasilije (VINČA Institute of Nuclear Sciences, 2016)
Calcium looping (CaL) is promising for large-scale CO2 capture in the power generation and industrial sectors due to the cheap sorbent used and the relatively low energy penalties achieved with this process. Because of the high operating temperatures the heat utilisation is a major advantage of the process, since a significant amount of power can be generated from it. However, this increases its complexity and capital costs. Therefore, not only the energy efficiency performance is important for these cycles, but also the capital costs must be taken into account, i.e. techno-economic analyses are required in order to determine which parameters and configurations are optimal to enhance technology viability in different integration scenarios. In this study the integration scenarios of CaL cycles and natural gas combined cycles (NGCC) are explored. The process models of the NGCC and CaL capture plant are developed to explore the most promising scenarios for NGCC-CaL integration with regards to efficiency penalties. Two scenarios are analysed in detail, and show that the system with heat recovery steam generator (HRSG) before and after the capture plant exhibited better performance of 49.1% efficiency compared with that of 45.7% when only one HRSG is located after the capture plant. However, the techno-economic analyses showed that the more energy efficient case, with two HRSGs, implies relatively higher cost of electricity (COE), 44.1€/MWh, when compared to that of the reference plant system (33.1€/MWh). The predicted cost of CO2 avoided for the case with two HRSGS is 29.3 €/ton CO2.
Keywords: NGCC; calcium looping; efficiency penalty; techno-economic analysis